1999
DOI: 10.1073/pnas.96.15.8511
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of apoptosis signal-regulating kinase 1-induced cell death by 14-3-3 proteins

Abstract: Apoptosis signal-regulating kinase 1 (ASK1) is a pivotal component of a signaling pathway induced by many death stimuli, including tumor necrosis factor ␣, Fas, and the anticancer drugs cisplatin and paclitaxel. Here we report that ASK1 proapoptotic activity is antagonized by association with 14-3-3 proteins. We found that ASK1 specifically bound 14-3-3 proteins via a site involving Ser-967 of ASK1. Interestingly, overexpression of 14-3-3 in HeLa cells blocked ASK1-induced apoptosis whereas disruption of the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
299
1
4

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 339 publications
(310 citation statements)
references
References 47 publications
6
299
1
4
Order By: Relevance
“…ASK1 is regulated either positively or negatively depending on its binding proteins. 12,13,15,[18][19][20][21][22][23][24][25] ASK1 is regulated by phosphorylation at several Ser/Thr/Tyr residues. Phosphorylation at Thr-838 leads to activation of ASK1, whereas phosphorylation at Ser-83, Ser-967, or Ser-1034 inactivates ASK1.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…ASK1 is regulated either positively or negatively depending on its binding proteins. 12,13,15,[18][19][20][21][22][23][24][25] ASK1 is regulated by phosphorylation at several Ser/Thr/Tyr residues. Phosphorylation at Thr-838 leads to activation of ASK1, whereas phosphorylation at Ser-83, Ser-967, or Ser-1034 inactivates ASK1.…”
mentioning
confidence: 99%
“…Phosphorylation at Thr-838 leads to activation of ASK1, whereas phosphorylation at Ser-83, Ser-967, or Ser-1034 inactivates ASK1. 24,[26][27][28] ASK1 is basally phosphorylated at Ser-967 by an unidentified kinase, and 14-3-3 binds to this site to inhibit ASK1. 24 Phosphorylation at Ser-83 is known to be catalyzed by Akt or PIM1.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…29 The mechanism by which stress stimuli activate ASK1 is not fully understood. ASK1 activation appears to involve several sequential steps including association with activators such as TRAF2 24,30 and AIP1, 31,32 release of cellular inhibitors such as thioredoxin and 14-3-3, [33][34][35] and ASK1 oligomerization/autophosphorylation at Thr845. 36 We have previously shown that HIPK1 is desumoylated in response to TNF leading to its cytoplasmic translocation and involvement in TNF-induced ASK-JNK signaling.…”
mentioning
confidence: 99%
“…21 The ASK1 activity is also inhibited by cytoplasmic p21 cip1/WAF1 that forms a complex with ASK1 23 and by the 14-3-3 protein that binds specifically to Ser-967 of ASK1. 24 Cells in various conditions would therefore respond differently, depending on a balance between the activated pathways within the cells.…”
Section: K709rmentioning
confidence: 99%